Community of the Transfiguration : the journey of a new monastic community - Dekar, Paul R. (Cambridge : Lutterworth, 2008)
In the 1930s, German theologian Dietrich Bonhoeffer anticipated the restoration of the Church after the coming Second World War through a new kind of monasticism, a way of life of uncompromising adherence to the Sermon on the Mount in imitation of Christ. Since then, the renewal of Christian monasticism has become a great spiritual movement. Imbued with a love for God and neighbor, and with a healthy self-love, people are going to monasteries to deepen their relationship with God, to pray, and to find peace. While some monastic institutions are suffering a decline in traditional vocations, man.
The new monasticism -- History of Holy Transfiguration Monastery -- Practices of Holy Transfiguration Monastery -- Theology of the resolve -- Why the new monasticism matters -- Appendix: Prayers from HTM.
Includes bibliographical references (pages 155-162).
Description based on print version record.
Master record variable field(s) change: 072
Keywords: Community of the Transfiguration (Breakwater, Vic.) -- History; Religious communities -- Australia -- Victoria; Monasticism and religious orders -- Australia -- Victoria; Monastic and religious life -- Australia -- Victoria; Spiritual life -- Baptists; RELIGION / Institutions & Organizations; Community of the Transfiguration; Religious communities -- Australia -- Victoria; Religious communities; ARCHITECTURE / Buildings / Religious; Electronic books